2008
DOI: 10.1890/07-0015.1
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Treatments Affect Mountain Pine Beetle Abundance and Woodpecker Foraging Behavior

Abstract: In British Columbia, Canada, management efforts used to control mountain pine beetle (Dendroctonus ponderosae Hopkins) outbreaks have included treatment of infested trees with an organic arsenic pesticide, monosodium methanearsonate (MSMA). Cumulative pesticide applications over a large geographic area have generated concerns about arsenic loading in the environment and potential toxicity to nontarget wildlife. We investigated woodpecker foraging patterns in infested stands with and without MSMA treatment usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Previous studies suggest that Magellanic woodpeckers feed preferentially on standing trees that exhibit an advanced decay stage [ 32 , 34 , 38 , 39 ]. These preferences are consistent with natural and experimental studies that demonstrate the ability of woodpeckers to recognize the type and amount of food (e.g., larvae) present in trees (e.g., [ 40 42 ]). Although theoretical studies suggest that foraging woodpeckers respond perceptually and cognitively to habitat heterogeneity over different spatial scales [ 43 ], the spatio-temporal scales at which woodpeckers assess the tree quality in the wild remains to be determined.…”
Section: Introductionsupporting
confidence: 87%
“…Previous studies suggest that Magellanic woodpeckers feed preferentially on standing trees that exhibit an advanced decay stage [ 32 , 34 , 38 , 39 ]. These preferences are consistent with natural and experimental studies that demonstrate the ability of woodpeckers to recognize the type and amount of food (e.g., larvae) present in trees (e.g., [ 40 42 ]). Although theoretical studies suggest that foraging woodpeckers respond perceptually and cognitively to habitat heterogeneity over different spatial scales [ 43 ], the spatio-temporal scales at which woodpeckers assess the tree quality in the wild remains to be determined.…”
Section: Introductionsupporting
confidence: 87%
“…Arsenic accumulation was similarly negligible in mice living in a contaminated seasonal wetland, whose diet consisted of seeds, plants, and arthropods that accumulated significant concentrations of arsenic (up to 0.419 mg kg −1 in arthropod prey) [23]. In contrast, studies addressing the affects of organoarsenical pesticides on woodpeckers and their prey, the mountain pine beetle, found that the birds accumulated potentially toxic levels of arsenic from the beetles [24], and that these levels caused both lethal [25] and sublethal [26] effects. The much more toxic effects of arsenic moving up the food chain in these studies may be the result of the organic form of arsenic in which beetles and birds were exposed versus inorganic forms in the Hopkins et al [22] and Torres and Johnson [23] studies, as well as the concentrations accumulated in the mountain pine beetles.…”
Section: Discussionmentioning
confidence: 99%
“…The trophic transfer of arsenic between an invertebrate prey and insect [16][19] or vertebrate [20], [21] predators has been documented for aquatic systems. However, in terrestrial systems, trophic transfer of arsenic has only been evaluated for movement to vertebrate predators [22][26].…”
Section: Introductionmentioning
confidence: 99%
“…As the beetles are dead, the trap tree does not have to be burned on site or removed, but simply allowed to decompose. MSMA treatment was favoured in British Columbia, because it was effective, relatively inexpensive and easy to apply in remote areas (British Columbia Ministry of Forests 1995;Morrissey et al 2008). From 1995 to 2004, 5080 kg of MSMA was applied to almost 500 000 trees in British Columbia for mountain pine beetle control (Morrissey et al 2007).…”
Section: Chemical Control Of Bark and Wood Boring Insectsmentioning
confidence: 99%